PENGARUH TINGKAT PENDIDIKAN, KESEHATAN DAN PENDAPATAN TERHADAP KEMISKINAN DI PROVINSI JAMBI - Evi Adriani; Wahyudi Wahyudi (Universitas Batanghari Jambi, 2015)
The purpose of this research is to know the influence from the level of education , health , and income to poverty at 2000-2014 period in Jambi province. Method and a tool used in this research is the double regression with SPSS 20 program . From the calculation known that the variable levels of education ( X1 ) and income ( X3 ) have negative impact to poverty ( Y ) , in other words if the level of education and income increased, poverty will decline in Jambi province .The size of the influence of each variable levels of education ( X1 ) and income (X3) is 0,578 and 1,773 .While , variable health (X2) have a positive impact to poverty in Jambi province with coefficient is 1,315. Also known that from the calculations stimultaneously a variable degree in education , health , and income have significant on poverty in Jambi province , but only degree in education have significant in partially.Keywords : Poverty, level educational, income, health